The Reverse Subsidy`s Impact of United Territorial Community`s Budget Generations - Horoshkova, Lidiia; Volkov, Volodymyr; Kapranova, Larisa; Komelina, Anna (International Journal of Engineering and Technology, 2018)
Critical analysis of the fiscal equalization system proved that its main disadvantages are a real threat to UTCs.The comparison of UTCs income growth trends with the reverse subsidies` growth rate revealed that over the period from 2015 to 2017 the income growth rate slowed down accompanied by the simultaneous growth of reverse subsidy to 25% of its amount.It was proposed to determine the permissible limits of the reverse subsidy correlated to the UTC per capita income growth rate.It was proved that to describe the dynamics of UTC income it is expedient to use not the exponential law (hard model), but the logistic model (soft model).It was offered to determine the safe limits of UTC financial position`s adjustment with the help of the logistic model ensuring sustainable development.Conditions for the external impact on the UTC system in the form of reverse subsidy were shaped. Safe limits for its amounts` adjustments were defined as well. It was proved that 50% of UTC income is critical amount of the reverse subsidy. The estimated permissible amount of the reverse subsidy is no more than 25% of UTC income.It was shown that ensuring of financially substantial UTC`s sustainable development is possible, if flexible, financially proved approach when setting the reverse subsidy amount, is used.Â Â